Global citizenship and the importance of education in a globally integrated world. (20th October 2017) - Smith, William C.; Fraser, Pablo; Chykina, Volha; Ikoma, Sakiko; Levitan, Joseph; Liu, Jing; Mahfouz, Julia
ABSTRACT: As national borders dissipate and technology allows different cultures and nationalities to communicate on a regular basis, more individuals are self-identifying as a global citizen. Using Social Network Analysis and multi-level modelling, this study explores factors associated with global citizen affinity and finds that education plays an important, perhaps the most important, role in individual's affinity towards this self-identification. Results clearly indicate that more education, not national economic or social integration, is more closely associated with an individual's positive identity as a global citizen. Additionally, the magnitude of the education effect is greater in more socially integrated societies.